‘We mean more than what we say on air’: interactional metadiscourse resources in television talk shows - Emmanuel Nii Adama Mensah; Christiana Hammond; Albert Agbesi Wornyo (Cogent Social Sciences)
This study explores the interactional metadiscourse resources employed on a Ghanaian television talk show and the communicative functions of these resources in persuading the target audience of the show. Five episodes of the television talk show prior to the 2020 presidential and parliamentary elections in Ghana were gathered as data and qualitatively analyzed using Hyland’s metadiscourse theory. The findings indicate that interlocutors on the talk show employed various interactional metadiscourse resources to indicate their stance toward propositions as well as their audience. The findings further revealed that the show is a persuasive arena for social commentators and representatives of political parties to exert rhetorical appeals of logos (rationality), ethos (credibility), and pathos (affection) on the audience. This study contributes to the literature on metadiscourse resources and concludes that television talk shows are permeating avenues for socio-political interlocutors to propagate their ideologies and assert their relevance in discussing issues of importance to their audiences. This study has implications for student teaching in communication and media studies. It recommends that interlocutors of television talk shows should be intentional in their on-air communicative engagements since ‘they mean more than what they actually say’ by their use of interactional metadiscourse resources.